CuY molecular sieve adsorbent for removing thiophene and preparation method thereof

By using small molecule amino acids as ligands and heat treatment activation technology in CuY molecular sieve adsorbents, the problem of insufficient number of active components in the adsorbents is solved, and the adsorption performance and desulfurization efficiency of thiophene are significantly improved, which is suitable for the deep removal of thiophene in coked benzene.

CN119500062APending Publication Date: 2025-02-25TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411594774.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-10
Publication Date
2025-02-25

Smart Images

  • Figure CN119500062A_ABST
    Figure CN119500062A_ABST
Patent Text Reader

Abstract

The invention discloses a CuY molecular sieve adsorbent for removing thiophene, which is prepared by the following steps: adding a Y-type molecular sieve into a metal complex solution of a micromolecular amino acid ligand and a copper salt solution, carrying out ion exchange to obtain a CuY molecular sieve adsorbent precursor, and carrying out heat treatment activation to obtain the CuY molecular sieve adsorbent. According to the present invention, the ligand and the metal species are chelated to regulate the setting of Cu in the Y-type molecular sieve, and the heat treatment activation is performed to make the CuY molecular sieve achieve the self-reduction of Cu (II) into Cu (I), and produce more Cu (I) active sites in the supercage, such that the desulfurization performance of the adsorbent is improved, and the deep removal of thiophene in coking benzene is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coking benzene purification, and relates to a desulfurization adsorbent for coking benzene, and in particular to a CuY molecular sieve adsorbent capable of deeply removing thiophene from coking benzene. Background Art

[0003] The presence of thiophene sulfides in coking benzene can cause catalyst poisoning and equipment corrosion, which seriously limits the subsequent utilization of coking benzene. Deep removal of thiophene in coking benzene is crucial to broaden its scope of use.

[0004] Selective adsorption is one of the most promising desulfurization technologies for removing thiophene from coking benzene. It uses adsorbents to selectively remove trace thiophene. It has the advantages of high desulfurization accuracy, low environmental pollution, and operability at room temperature and pressure, and does not require the use of expensive hydrogen.

[0005] Among many adsorbents, CuY molecular sieve is widely used in the field of fine desulfurization, but its desulfurization performance is closely related to the location of copper species in the molecular sieve cage (super cage, sodalite cage and hexagonal cage). Among them, the super cage structure has a diameter of 0.74nm, which is larger than the size of thiophene molecules (0.56nm), and is the main site for adsorption desulfurization, while the diameters of sodalite cages and hexagonal cages are only 0.28nm and 0.23nm, which are smaller than the molecular size of thiophene. Thiophene cannot enter, making it difficult for the active sites in the structure to function. Therefore, in order to make more metal Cu become effective active sites, it is necessary to regulate the location of Cu in the Y-type molecular sieve and confine it to a super cage larger than the thiophene molecule to further improve the adsorption performance of thiophene sulfides in coking benzene.

[0006] At the same time, by regulating the transfer mode of electrons on the metal valence electron layer, the adsorption performance of thiophene can also be regulated. Professor Ralph T. Yang's research group believes that according to the adsorption mechanism, the deep desulfurization of CuY molecular sieve adsorbent is due to the Cu(I) ion ([Ar]3d 10 4s 0 ) and thiophene. The π electrons of thiophene can enter the empty s orbital of the copper ion to form a σ bond; the electrons in the d orbital of the copper ion will enter the anti-π orbital (π*) of thiophene to form a d-π* antibond, so that thiophene is adsorbed on the CuY molecular sieve adsorbent in a π complexed manner. Experimental data and molecular orbital (MO) calculations show that the π complexation between Cu(I) and organic sulfur molecules is stronger. Therefore, in order to further improve the desulfurization performance of the CuY molecular sieve adsorbent, more Cu(I) active sites need to be created.

[0007] Yun Zu et al. (Facile fabrication of a superior Cu(I)-NH4Y zeoliteadsorbent for improving thiophene adsorption selectivity in the presence ofaromatics or olefins[J]. Chem. Eng. J , 2020, 401: 126112.) Using NH4Y as raw material, Cu(I)-NH4Y molecular sieves with different Cu loadings were prepared by liquid phase ion exchange method, and new adsorption active sites ([Cu + ···NH3···H + ]), in the presence of aromatics and olefins, the adsorbent's adsorption selectivity for thiophene is significantly improved. However, this method requires the use of highly flammable reducing H2, which is highly dangerous.

[0008] Zhao Jinchuan (Regulation of Ce placement in Y-type molecular sieves and its effect on thiophene removal performance in benzene [D]. Taiyuan: Taiyuan University of Technology, 2023.) By using amino acids as organic ligands to coordinate with Ce ions and regulating their placement in Y-type molecular sieves, GCeY adsorbent with the best desulfurization performance was prepared, and it was proved that the type of amino acid has no significant effect on the desulfurization efficiency of the adsorbent. Although this method effectively regulates the placement of Ce ions in the supercage, it does not create a Ce that is conducive to thiophene adsorption. 4+ Active sites: The actual loaded metal species cannot be effectively utilized, and the utilization rate of active sites is low.

[0009] Therefore, the key issues to be solved in increasing the adsorption performance of molecular sieve adsorbents for sulfur-containing compounds are to solve the problem that most of the active metal species in the adsorbent are located in sodalite cages and hexagonal cages, and the content of them in super cages is relatively low, and to increase the proportion of Cu(I) active sites in the CuY molecular sieve adsorbent and improve the utilization rate of active components. Summary of the invention

[0010] The purpose of the present invention is to provide a CuY molecular sieve adsorbent for removing thiophene, and a method for preparing the adsorbent, so as to solve the problems of accurate positioning of metal components in the Y-type molecular sieve cage and small number of active components in existing desulfurization adsorbents.

[0011] Providing the application of the CuY molecular sieve adsorbent in removing thiophene in coking benzene is another object of the present invention.

[0012] In order to achieve the above-mentioned purpose of the invention, it is necessary to prepare the CuY molecular sieve adsorbent by a simple method, which not only realizes the location of the metal active components in the supercage, but also realizes the reduction of the active components from Cu(II) to Cu(I), thereby improving the utilization rate of the active components.

[0013] To this end, the present invention first provides a method for preparing a CuY molecular sieve adsorbent for removing thiophene, the method specifically comprising:

[0014] A small molecule amino acid is used as a ligand and added to a copper salt solution to form a metal complex solution;

[0015] Placing the Y-type molecular sieve raw powder in the metal complex solution, and obtaining the CuY molecular sieve adsorbent precursor after sufficient ion exchange;

[0016] The CuY molecular sieve adsorbent precursor is heat-treated and activated to obtain a product CuY molecular sieve adsorbent.

[0017] Furthermore, the small molecule amino acid is specifically an amino acid with a molecular weight less than 120.

[0018] Furthermore, the small molecule amino acid is preferably any one of alanine, glycine or serine.

[0019] Copper ion Cu 2+ The coordination ability is the strongest among the first series of transition metals, and the amino nitrogen and carboxyl oxygen of the amino acid can form coordination bonds with the copper ion. The small molecule amino acids selected in the present invention can form monodentate or bidentate complexes when coordinated with the copper ion, and the logarithmic values ​​of the stability constants corresponding to the three bidentate complexes are all greater than 10, which have good stability and are conducive to ion exchange with the Y-type molecular sieve.

[0020] Furthermore, the copper salt solution is an aqueous solution prepared with any water-soluble copper salt, and the present invention has no special limitation thereto.

[0021] Furthermore, the copper salt solution is preferably any one of copper nitrate solution, copper sulfate solution and copper acetate solution.

[0022] Furthermore, in the metal complex solution of the present invention, the molar ratio of copper salt to ligand is preferably 1:1-2.

[0023] Furthermore, the Y-type molecular sieve described in the present invention is NaY molecular sieve or HY molecular sieve.

[0024] Furthermore, the ion exchange of the present invention is preferably carried out at 80-100°C. 2+The ion radius is 73pm. Low ion exchange temperature will result in a longer time for complete exchange, while high temperature will cause a certain degree of dealumination of the molecular sieve and cause energy waste.

[0025] Furthermore, the ion exchange time is preferably 4 to 6 hours.

[0026] Furthermore, the present invention performs heat treatment activation on the CuY molecular sieve adsorbent precursor at 350-450°C.

[0027] Furthermore, the heat treatment activation time is preferably 2 to 5 hours.

[0028] The present invention adopts the method to prepare a highly efficient CuY molecular sieve adsorbent, which enables more metal Cu(II) to be self-reduced to Cu(I) and located in the molecular sieve super cage, thereby improving the utilization rate of copper active sites.

[0029] Based on the characteristics of the CuY molecular sieve adsorbent of the present invention having many active sites, large adsorption capacity for thiophene and high desulfurization efficiency, it is suitable for removing thiophene sulfides in coking benzene.

[0030] When the CuY molecular sieve adsorbent of the present invention is used to remove thiophene sulfide, the metal Cu located in the super cage mainly plays an adsorption role and adsorbs thiophene through π-complexation.

[0031] The present invention firstly prepares the CuY molecular sieve adsorbent by selecting an amino acid ligand with a suitable molecular weight, so that most of the copper species can fall into the super cage of the molecular sieve to become effective active sites, rather than being too large to be exchanged into the molecular sieve, thereby further improving the utilization rate of the active components, enhancing the desulfurization activity of the adsorbent, and realizing the removal of thiophene in coking benzene.

[0032] Secondly, the present invention achieves complete decomposition of the metal complex and promotes the self-reduction of copper species by regulating the activation temperature and time of the heat treatment. The ammonia generated by the heat treatment of the metal complex promotes the generation and uniform dispersion of the active species Cu(I), resulting in more Cu(I) adsorbing thiophene through π-complexation, increasing the adsorption active sites of the molecular sieve, allowing more Cu(I) to exchange ions with the cationic active sites SII, SIII or SIII′ of the molecular sieve supercage, further improving the ion exchange degree of the adsorbent, significantly improving the desulfurization performance of the adsorbent, and effectively avoiding the problems of low content of self-reduced copper species when the heat treatment temperature of the adsorbent precursor is low, agglomeration of copper species when the heat treatment temperature is high, and migration of copper species caused by long heat treatment time.

[0033] The present invention uses a simple and easy preparation method, which not only realizes that the active species Cu is located in the super cage of the Y-type molecular sieve adsorbent, but also promotes the self-reduction of the Cu species, creates more Cu(I) and thiophene for adsorption, and improves the desulfurization performance of the adsorbent. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a graph of the desulfurization efficiency of thiophene adsorbed by the molecular sieve adsorbent prepared in each embodiment and comparative example.

[0035] Figure 2 It is the XPS spectra of the molecular sieve adsorbent prepared in Example 1 and Comparative Example 5. Implementation

[0036] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.

[0037] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Technical personnel in the field can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.

[0038] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art.

[0039] The following examples of the present invention prepare CuY molecular sieve adsorbent according to the following method:

[0040] a) Select Y-type molecular sieve raw powder;

[0041] b) preparing a copper salt solution of a certain concentration and mixing it with different types of small molecule amino acid ligands in a certain proportion to form a metal complex solution;

[0042] c) mixing Y-type molecular sieve raw powder and metal complex solution in a certain proportion, performing ion exchange at a certain temperature, and obtaining CuY molecular sieve adsorbent precursor through washing, filtering and drying;

[0043] d) The CuY molecular sieve adsorbent precursor is activated by heat treatment to obtain a product CuY molecular sieve adsorbent.

[0044] As a preferred embodiment, the Y-type molecular sieve in step a) of the present invention is NaY molecular sieve or HY molecular sieve.

[0045] As a preferred embodiment, the concentration of the copper salt solution in step b) of the present invention is 0.1-0.15 mol / L, and the molar ratio of the copper salt to the ligand in the metal complex solution is 1:1-2.

[0046] As a preferred embodiment, in step c) of the present invention, the solid-liquid mass volume ratio (g / mL) of the Y-type molecular sieve raw powder to the metal complex solution is 1:10-15, and the ion exchange is carried out at 80-100°C for 4-6h.

[0047] As a preferred embodiment, the heat treatment activation temperature in step d) of the present invention is controlled at 350-450° C., the heating rate is controlled at 2-5° C. / min, and the heat treatment activation time is 2-5 h.

[0048] The present invention uses a thiophene-benzene solution to test the adsorption desulfurization effect of the prepared CuY molecular sieve adsorbent. Specifically, a certain amount of CuY molecular sieve adsorbent is placed in the thiophene-benzene solution, the ampoule is sealed, and placed on a shaker. The adsorption is oscillated for 24 hours at an adsorption temperature of 25 to 30°C and a pressure of normal pressure to reach adsorption equilibrium. The residual thiophene concentration in the solution is detected by gas chromatography (GC-FPD). Example

[0049] Example 1

[0050] Prepare 50 mL of 0.1 mol / L copper acetate solution.

[0051] Alanine was dissolved in water to prepare 50 mL of a ligand solution with a concentration of 0.2 mol / L.

[0052] The copper acetate solution and the ligand solution were mixed, and stirred at 30° C. for 30 min to obtain a mixed solution.

[0053] The mixed solution and 10 g of NaY molecular sieve with a silicon-aluminum molar ratio of 2.78 were added into a stirred three-necked flask connected to a condenser, and heated to 97° C. with mechanical stirring at 200-300 r / min for ion exchange reaction for 4 hours.

[0054] The reaction product was cooled to room temperature, filtered and washed with deionized water until neutral, the solid was collected, dried in an oven at 120°C for 12 h, and then placed in a tubular furnace, heated to 400°C at a rate of 5°C / min in an air atmosphere for heat treatment activation for 4 h to prepare molecular sieve adsorbent A.

[0055] Example 2

[0056] Prepare 50 mL of 0.1 mol / L copper acetate solution.

[0057] Alanine was dissolved in water to prepare 50 mL of a ligand solution with a concentration of 0.2 mol / L.

[0058] The copper acetate solution and the ligand solution were mixed, and stirred at 30° C. for 30 min to obtain a mixed solution.

[0059] The mixed solution and 10 g of NaY molecular sieve with a silicon-aluminum molar ratio of 2.78 were added into a stirred three-necked flask connected to a condenser, and heated to 97° C. with mechanical stirring at 200-300 r / min for ion exchange reaction for 4 hours.

[0060] The reaction product was cooled to room temperature, filtered and washed with deionized water until neutral, the solid was collected, dried in an oven at 120°C for 12 h, and then placed in a tubular furnace and heated to 450°C at a rate of 5°C / min in an air atmosphere for heat treatment activation for 4 h to prepare molecular sieve adsorbent B.

[0061] Example 3

[0062] Prepare 50 mL of 0.1 mol / L copper acetate solution.

[0063] Dissolve glycine in water to prepare 50 mL of a ligand solution with a concentration of 0.2 mol / L.

[0064] The copper acetate solution and the ligand solution were mixed, and stirred at 30° C. for 30 min to obtain a mixed solution.

[0065] The mixed solution and 10 g of NaY molecular sieve with a silicon-aluminum molar ratio of 2.78 were added into a stirred three-necked flask connected to a condenser, and heated to 97° C. with mechanical stirring at 200-300 r / min for ion exchange reaction for 4 hours.

[0066] The reaction product was cooled to room temperature, filtered and washed with deionized water until neutral, the solid was collected, dried in an oven at 120°C for 12 h, and then placed in a tubular furnace, heated to 400°C at a rate of 5°C / min in an air atmosphere for heat treatment activation for 4 h to prepare molecular sieve adsorbent C.

[0067] Example 4

[0068] Prepare 50 mL of 0.1 mol / L copper acetate solution.

[0069] Serine was dissolved in water to prepare 50 mL of a ligand solution with a concentration of 0.2 mol / L.

[0070] The copper acetate solution and the ligand solution were mixed, and stirred at 30° C. for 30 min to obtain a mixed solution.

[0071] The mixed solution and 10 g of NaY molecular sieve with a silicon-aluminum molar ratio of 2.78 were added into a stirred three-necked flask connected to a condenser, and heated to 97° C. with mechanical stirring at 200-300 r / min for ion exchange reaction for 4 hours.

[0072] The reaction product was cooled to room temperature, filtered and washed with deionized water until neutral, the solid was collected, dried in an oven at 120°C for 12 h, and then placed in a tubular furnace and heated to 400°C at a rate of 5°C / min in an air atmosphere for heat treatment activation for 4 h to prepare molecular sieve adsorbent D.

[0073] Comparative Example 1

[0074] Prepare 50 mL of 0.1 mol / L copper acetate solution.

[0075] Alanine was dissolved in water to prepare 50 mL of a ligand solution with a concentration of 0.2 mol / L.

[0076] The copper acetate solution and the ligand solution were mixed, and stirred at 30° C. for 30 min to obtain a mixed solution.

[0077] The mixed solution and 10 g of NaY molecular sieve with a silicon-aluminum molar ratio of 2.78 were added into a stirred three-necked flask connected to a condenser, and heated to 97° C. with mechanical stirring at 200-300 r / min for ion exchange reaction for 4 hours.

[0078] The reaction product was cooled to room temperature, filtered and washed with deionized water until neutral, the solid was collected, dried in an oven at 120°C for 12 h, and then placed in a tubular furnace and heated to 250°C at a rate of 5°C / min in an air atmosphere for heat treatment activation for 4 h to prepare molecular sieve adsorbent A1.

[0079] Comparative Example 2

[0080] Prepare 50 mL of 0.1 mol / L copper acetate solution.

[0081] Alanine was dissolved in water to prepare 50 mL of a ligand solution with a concentration of 0.2 mol / L.

[0082] The copper acetate solution and the ligand solution were mixed, and stirred at 30° C. for 30 min to obtain a mixed solution.

[0083] The mixed solution and 10 g of NaY molecular sieve with a silicon-aluminum molar ratio of 2.78 were added into a stirred three-necked flask connected to a condenser, and heated to 97° C. with mechanical stirring at 200-300 r / min for ion exchange reaction for 4 hours.

[0084] The reaction product was cooled to room temperature, filtered and washed with deionized water until neutral, the solid was collected, dried in an oven at 120°C for 12 h, and then placed in a tubular furnace and heated to 550°C at a rate of 5°C / min in an air atmosphere for heat treatment and activation for 4 h to prepare molecular sieve adsorbent A2.

[0085] Comparative Example 3

[0086] Prepare 50 mL of 0.1 mol / L copper acetate solution.

[0087] Alanine was dissolved in water to prepare 50 mL of a ligand solution with a concentration of 0.2 mol / L.

[0088] The copper acetate solution and the ligand solution were mixed, and stirred at 30° C. for 30 min to obtain a mixed solution.

[0089] The mixed solution and 10 g of NaY molecular sieve with a silicon-aluminum molar ratio of 2.78 were added into a stirred three-necked flask connected to a condenser, and heated to 97° C. with mechanical stirring at 200-300 r / min for ion exchange reaction for 4 hours.

[0090] The reaction product was cooled to room temperature, filtered and washed with deionized water until neutral, the solid was collected, dried in an oven at 120°C for 12 h, and then placed in a tubular furnace and heated to 400°C at a rate of 5°C / min in an air atmosphere for heat treatment activation for 6 h to prepare molecular sieve adsorbent A3.

[0091] Comparative Example 4

[0092] Prepare 50 mL of 0.1 mol / L copper acetate solution.

[0093] Dissolve EDTA in water to prepare 50 mL of 0.2 mol / L ligand solution.

[0094] The copper acetate solution and the ligand solution were mixed, and stirred at 30° C. for 30 min to obtain a mixed solution.

[0095] The mixed solution and 10 g of NaY molecular sieve with a silicon-aluminum molar ratio of 2.78 were added into a stirred three-necked flask connected to a condenser, and heated to 97° C. with mechanical stirring at 200-300 r / min for ion exchange reaction for 4 hours.

[0096] The reaction product was cooled to room temperature, filtered and washed with deionized water until neutral, the solid was collected, dried in an oven at 120°C for 12 h, and then placed in a tubular furnace, heated to 400°C at a rate of 5°C / min in an air atmosphere for heat treatment and activation for 4 h to prepare molecular sieve adsorbent E.

[0097] Comparative Example 5

[0098] Prepare 100 mL of 0.1 mol / L copper acetate solution and add it together with 10 g of NaY molecular sieve with a silicon-aluminum molar ratio of 2.78 into a stirred three-necked flask connected to a condenser. Heat to 97°C with mechanical stirring at 200-300 r / min and carry out ion exchange reaction for 4 hours.

[0099] The reaction product was cooled to room temperature, filtered and washed with deionized water until neutral, the solid was collected, dried in an oven at 120°C for 12 h, and then placed in a tubular furnace, heated to 400°C at a rate of 5°C / min in an air atmosphere for heat treatment and activation for 4 h to prepare a conventional molecular sieve adsorbent CuY.

[0100] Application Example 1

[0101] Weigh 0.5 g of thiophene and dissolve it in 1000 mL of benzene to prepare a thiophene-benzene solution with a thiophene concentration of 500 ppm.

[0102] 0.1 g of each of the molecular sieve adsorbents prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were weighed, added to the above thiophene-benzene solution at a liquid-to-drug ratio of 10 mL / g, and sealed in an ampoule.

[0103] The shaking water bath temperature was set to 30°C and the shaking frequency to 100 rpm. The ampoule was placed on the shaking table and shaken for 24 h to achieve adsorption equilibrium.

[0104] The residual thiophene concentration in the solution was detected by gas chromatography (GC-FPD). The desulfurization efficiency of each molecular sieve adsorbent was calculated based on the change in thiophene concentration in the solution before and after adsorption. The specific results are as follows: Figure 1 shown.

[0105] Figure 1 The desulfurization efficiencies of the molecular sieve adsorbents prepared in Examples 1 to 4 for thiophene are 57.6%, 57.1%, 44.8%, and 42.4%, respectively. The desulfurization efficiencies of the molecular sieve adsorbents prepared in Comparative Examples 1 to 5 for thiophene are 28.5%, 34.6%, 30.5%, 33.4%, and 25.8%, respectively.

[0106] Figure 1 In the embodiment 1 and the embodiment 2, based on the complexation of alanine (C3H7NO2) with copper, and selecting appropriate heat treatment temperature (400°C and 450°C) and heat treatment time (4h), the molecular sieve adsorbents A and B prepared have high desulfurization efficiency, reaching 57.6% and 57.1%, which are significantly higher than the molecular sieve adsorbent CuY prepared by conventional method in comparative example 5.

[0107] This is because when the adsorbent precursor is heat-treated at a suitable temperature, the copper complex has been completely decomposed, and the generated ammonia can promote the self-reduction of most copper species to Cu(I) and stably settle in the supercage, and the adsorption performance will also tend to be stable.

[0108] Figure 2 The Cu 2p XPS spectra of molecular sieve adsorbent A and conventional CuY are further provided to obtain the valence distribution of related copper species in the Y-type molecular sieve. The peaks at binding energies of 933 eV and 936 eV in the figure can be attributed to the Cu and CuY adsorbents, respectively. + 2p 3 / 2 and Cu 2+ 2p 3 / 2 .

[0109] The ratio of monovalent copper species to divalent copper species in molecular sieve adsorbent A and conventional CuY + / Cu 2+ like Figure 2 As shown, in Example 1, the Cu + / Cu 2+ The ratio of is significantly greater than that of conventional CuY molecular sieves, indicating that molecular sieve adsorbent A has more Cu + Therefore, using alanine as a ligand to chelate copper and selecting a suitable heat treatment temperature is beneficial to increasing the number of active sites of effective monovalent copper species.

[0110] The desulfurization efficiency of the molecular sieve adsorbents C and D prepared by complexing the glycine ligand (C2H5NO2) and serine ligand (C3H7NO3) with copper in Examples 3 and 4 is also improved compared with the conventional molecular sieve adsorbent CuY. This shows that after the chelation of Cu and the ligand, more active copper falls into the super cage of the molecular sieve adsorbent and forms effective sites of Cu(I), which can be more fully contacted with thiophene, reflecting the importance of introducing Cu active sites by the ligand method in the present invention.

[0111] Compared with Example 1, when the heat treatment temperature of the adsorbent precursor in Comparative Example 1 was low, the copper complex was not completely decomposed, resulting in insufficient ammonia to promote the complete conversion of Cu(II) to Cu(I), and the proportion of Cu(I) in the adsorbent was low, so the desulfurization performance of adsorbent A1 was poor. In Comparative Example 2, although the heat treatment temperature of the adsorbent precursor was high, the copper complex was completely decomposed, and most of the copper species could be located in the supercage of the molecular sieve, but due to the high heat treatment temperature, the copper species in the supercage polymerized to generate dimeric Cu species [(Cu-O-Cu)] 2+ With binuclear copper species [(Cu-O2-Cu)] 2+ Etc., which makes the copper species unable to become an effective adsorption active site and also leads to the low desulfurization efficiency of adsorbent A2.

[0112] Compared with Example 1, in Comparative Example 3, due to the longer heat treatment time of the adsorbent precursor, although the conversion of Cu(II) to Cu(I) can be achieved, the copper species can easily migrate from the supercage to the sodalite cage and the hexagonal cage. The active species cannot stably exist in the supercage of the molecular sieve and cannot contact the thiophene molecules.

[0113] Compared with Example 1, Comparative Example 4 uses common EDTA ligands to complex with copper, and the desulfurization performance of the obtained molecular sieve adsorbent E is relatively low. During the experiment, it was found that after the EDTA ligands were complexed with copper, the color of the obtained adsorbent was still white, and the copper content (mass percentage) was less than 0.005 (wt%) after ICP testing. This is because EDTA (C 10 H 16 The four carboxyl groups (COOH) and two ethylenediamine groups (NH2CH2CH2NH2) of the Y-type molecular sieve (N2O8) molecule can participate in the complexation reaction of metal ions. After chelating with copper, it forms a very stable complex with a large molecular size. The copper complex cannot enter the cage of the Y-type molecular sieve, and the metal copper species cannot exchange ions with the Y-type molecular sieve, let alone make the metal Cu fall in the super cage. Therefore, EDTA cannot be used as a ligand to improve the desulfurization performance of the adsorbent. This shows that the ligand size is very important for the placement of copper in the Y-type molecular sieve. Only ligands with suitable molecular sizes are more conducive to improving the desulfurization efficiency of the molecular sieve adsorbent and allowing more metal active components to fall into the super cage.

[0114] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a CuY molecular sieve adsorbent, comprising: A small molecule amino acid is used as a ligand and added to a copper salt solution to form a metal complex solution; Placing the Y-type molecular sieve raw powder in the metal complex solution, and obtaining the CuY molecular sieve adsorbent precursor after sufficient ion exchange; The CuY molecular sieve adsorbent precursor is heat-treated and activated to obtain a product CuY molecular sieve adsorbent.

2. The method for preparing the CuY molecular sieve adsorbent according to claim 1, characterized in that The molecular weight of the small molecule amino acid is less than 120.

3. The method for preparing the CuY molecular sieve adsorbent according to claim 2, characterized in that The small molecule amino acid is any one of alanine, glycine or serine.

4. The method for preparing the CuY molecular sieve adsorbent according to claim 1, characterized in that The molar ratio of the copper salt to the ligand in the metal complex solution is 1:1-2.

5. The method for preparing the CuY molecular sieve adsorbent according to claim 1, characterized in that The Y-type molecular sieve is NaY molecular sieve or HY molecular sieve.

6. The method for preparing the CuY molecular sieve adsorbent according to claim 1, characterized in that The ion exchange is carried out at 80-100° C. for 4-6 hours.

7. The method for preparing the CuY molecular sieve adsorbent according to claim 1, characterized in that The heat treatment activation of the CuY molecular sieve adsorbent precursor is carried out at 350-450°C.

8. The method for preparing the CuY molecular sieve adsorbent according to claim 1, characterized in that Heat treatment activation time is 2 to 5 hours.

9. The CuY molecular sieve adsorbent prepared by the preparation method according to claim 1.

10. Use of the CuY molecular sieve adsorbent according to claim 9 as an adsorbent for removing thiophene sulfide from coking benzene.